2017
DOI: 10.1111/cei.12914
|View full text |Cite
|
Sign up to set email alerts
|

Ro52/TRIM21-deficient expression and function in different subsets of peripheral blood mononuclear cells is associated with a proinflammatory cytokine response in patients with idiopathic inflammatory myopathies

Abstract: The presence of anti-Ro52/tripartite motif 21 (Trim21) autoantibodies has been associated with a distinctive clinical profile and has gained value as a prognostic marker in idiopathic inflammatory myopathies (IIM). The aim of the present work was to analyse Ro52/Trim21 expression in different subsets of peripheral blood mononuclear cells (PBMCs) of patients with IIM, as well as the ubiquitination profile and its association with proinflammatory cytokine production. We included 18 patients with recent-onset IIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
10
0
3
Order By: Relevance
“…The dysregulation of Trim21 in different cells and tissues contributes to the pathogenesis of autoimmune diseases, such as systemic lupus erythematosus, systemic sclerosis and psoriasis and cancer 19,20,21. In idiopathic inflammatory myopathies, Trim21 expression is decreased in different subsets of peripheral blood monocytes; this downregulation is associated with a proinflammatory cytokine response 22. In inflammatory bowel disease, decreased Trim21 expression in inflamed patient mucosa promotes the differentiation of CD4 + T cells into T‐helper (Th)1 and Th17 cells, suggesting that Trim21 has an inhibitory role in mucosal inflammation 23.…”
mentioning
confidence: 99%
“…The dysregulation of Trim21 in different cells and tissues contributes to the pathogenesis of autoimmune diseases, such as systemic lupus erythematosus, systemic sclerosis and psoriasis and cancer 19,20,21. In idiopathic inflammatory myopathies, Trim21 expression is decreased in different subsets of peripheral blood monocytes; this downregulation is associated with a proinflammatory cytokine response 22. In inflammatory bowel disease, decreased Trim21 expression in inflamed patient mucosa promotes the differentiation of CD4 + T cells into T‐helper (Th)1 and Th17 cells, suggesting that Trim21 has an inhibitory role in mucosal inflammation 23.…”
mentioning
confidence: 99%
“…Among TRIM family members, TRIM21 acts not only as an E3 ubiquitin ligase on different target proteins, but also as a substrate in auto-ubiquitination, both leading to protein degradation [56,57,58]. In addition, TRIM21 is involved in cancer [59,60], inflammation [61,62,63,64], intracellular immunity, and autoimmunity [47,65,66,67]. Here, we validated the protein screen data for TRIM21, using two-way co-immunoprecipitation analysis of endoglin and TRIM21 in HUVECs and co-transfected CHO-K1 cells (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…We then tried to analyze the correlation of Ro52‐autoAb‐production and ILD. To achieve this goal, we tried to obtain mRo52‐autoAbs from DM patients because they are frequently complicated with ILD . We randomly selected 4 DM patients with severe ILD who also suffered from anti‐synthetase syndrome and had anti‐SS‐A, anti‐Jo‐1, or anti‐PL‐7 autoantibodies as well as Ro52‐autoAbs in their sera (Supporting Information Table ).…”
Section: Resultsmentioning
confidence: 99%
“…For the onset of ILD, multiple risk factors should be considered to be involved. One of the risk factors is autoantibodies; however, it has been reported that ILD‐related autoantibodies are not only anti‐Ro52 autoantibodies but also anti‐PL‐7 and anti‐Jo‐1 autoantibodies , among others. Thus, analysis of the involvement of anti‐PL‐7 and anti‐Jo‐1 autoantibodies in ILD may contribute to understanding the morbidity and severity of many PEP08‐negative patients.…”
Section: Discussionmentioning
confidence: 99%